Exercise alleviates hematopoietic stem cell injury following radiation via the carnosine/Slc15a2-p53 axis - Hao Zeng; Naicheng Chen; Fang Chen; Xiaoyi Zhong; Lijing Yang; Yukai Lu; Mo Chen; Mingqiang Shen; Song Wang; Shilei Chen; Jia Cao; Xi Zhang; et al. (Cell Communication and Signaling)
Abstract Ionizing radiation (IR) can cause severe dysfunction of hematopoietic stem cells (HSCs), leading to acute or prolonged myelosuppression. In recent years, physical exercise has been recognized as a healthy lifestyle as it can fight a variety of diseases. However, whether it provides protection against IR is not fully understood. In this study, we revealed that long-term moderate exercise mitigated IR-induced hematopoietic injury by generating carnosine from skeletal muscles. We found that exercised mice displayed reduced loss of HSC number and function after IR, accompanied by alleviated bone marrow damage. Interestingly, these effects were largely abrogated by specific deletion of carnosine synthase Carns1 in skeletal muscles. In contrast, carnosine treatment protected HSCs against IR-induced injury. Mechanistically, we demonstrated that exercise-generated carnosine was specifically transported to HSCs via Slc15a2 and then inhibited p53 transcriptional activity by directly interacting with its core DNA-binding domain, which led to downregulation of the p53 target genes p21 and Puma, thus promoting the proliferation and survival and inhibiting the senescence of irradiated HSCs. More importantly, a similar role of the carnosine/Slc15a2-p53 axis was observed in human cord blood-derived HSCs. Collectively, our data reveal that moderate exercise or carnosine supplementation may be potential antiradiation strategies.